Integrated beta model for bathtub-shaped hazard rate data. Issue 3 (2nd July 2016) - Lai, Chin-Diew; Jones, Geoff; Xie, Min
Abstract: In this paper, we introduce a new parametric distribution for modelling lifetime data with bathtub-shaped hazard rate, derived by representing the cumulative hazard as proportional to a generalized beta density. The distribution has a finite range, useful when there is a maximum possible lifetime, a common scenario when there are additional failure modes leading to failure after a certain time. Reliability and other distributional properties of the distribution are discussed. Parameter issues are also studied. The application of the model is illustrated by fitting the model to several data sets from the literature.